In HIV-infected patients, intestinal bacteria-derived products interfere with CD4+T cell regeneration - Korolevskaya, L. B.; Saidakova, E. V.; Shmagel, N. G.; Shmagel, K. V. (Medit͡s︡inskai͡a︡ immunologii͡a, 2023)
Despite successful suppression of viral replication by antiretroviral drugs there is no significant increase in the number of peripheral CD4 + T lymphocytes in some HIV-infected patients (immune nonresponse to therapy). One of the crucial factors for immunodeficiency aggravation is immune activation developing in response to the bacterial products entry into the bloodstream through the damaged intestinal barrier. Additionally, the intestinal microflora produces various solutes that accumulate in the blood and exhibit toxic properties. This work aimed to evaluate the effect of intestinal microbial products (para-cresol sulfate and indoxyl sulfate) on the number of CD4 + T lymphocytes in HIV-infected patients receiving antiretroviral therapy. The object of the study was the peripheral blood of HIV-infected subjects with different immune system restoration efficiency during the therapy. Uninfected donors were enrolled as healthy controls. Plasma concentrations of IL-6 (p = 0.012), IP-10 (p = 0.0004), and sCD14 (p = 0.003) in HIV-infected immune nonresponders were increased compared with those in individuals with effective restoration of CD4 + Tcells (immune responders). Although both groups of HIV-positive subjects did not differ in plasma lipopolysaccharide and I-FABP levels, para-cresol sulfate (p = 0.001) and indoxyl sulfate (p = 0.042) concentrations were increased in immune non-responders. In vitro experiments showed a negative dose-dependent effect of para-cresol sulfate and indoxyl sulfate on the viability and mitotic activity of CD4 + T lymphocytes. Thus, in HIV-infected patients with impaired regeneration of CD4 + T lymphocytes during antiretroviral therapy, a higher level of systemic inflammation is noted than in subjects responding to treatment with an increase in the number of CD4 + T cells. The severity of the intestinal barrier damage and the load of bacterial components released into the bloodstream are approximately the same in HIV-infected individuals with different efficiency of immune recovery in response to treatment. Simultaneously, the blood plasma of immune non-responders is significantly enriched with microbial products of intestinal origin: para-cresol sulfate and indoxyl sulfate. The significant decrease in the proliferative capacity of CD4 + T cells stimulated in vitro and the induction of their death in the presence of these toxins may be a reason for the ineffective restoration of the number of CD4 + T lymphocytes in HIV-infected individuals receiving antiretroviral therapy.